ANALISIS YURIDIS PERLINDUNGAN HUKUM PEMEGANG HAK ATAS MEREK YANG SAMA TERHADAP SATU KEGIATAN USAHA SEJENIS (Studi Kasus : Putusan Nomor 09/Pdt.Sus-Merek/2021/Pn.Niaga.Jkt.Pst) - El Rohman, Febrian; Sunarya, Sunarya; Pangestu, Ilham Aji (Lex Veritatis, 2023)
In this modern era, brands are important in distinguishing goods or services, the lack of protection of intellectual property provides benefits for other parties. In this study, the main problem is the protection of rights holders for brands that have similarities in principle and what are the legal consequences of disputes over the same trademark against one type of business. This research is a type of normative juridical research with analytical descriptive nature so that the primary data sources and secondary data sources are analyzed qualitatively. The results of the defendant's research have never asked the plaintiff's permission as the owner of the registered mark, therefore the defendant has used without the plaintiff's trademark rights. The plaintiffs are demanding compensation for the defendants and for the business activities to be terminated.